HUBUNGAN INTENSITAS KEBISINGAN DENGAN TEKANAN DARAH PADA PEKERJA AREA WORKSHOP - Mariman Tjendera; Isramilda Isramilda (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Noise in the workplace is often a separate problem for the workforce so that it can cause mental-emotional disturbance as well as the heart and circulatory system. According to the 2013 Basic Health Research, the prevalence of high blood pressure in Indonesia at the age of ≥18 years is 25.8%. So the researchers wanted to find a relationship between noise intensity and blood pressure. This research method was observational analytic with a cross-sectional approach conducted at PT. Bintang Intipersada Shipyard, Batam City. The sampling technique was a total sampling with a population of 100 workers in 2018 and obtained results of 61 workers determined by inclusion and exclusion criteria. The results of the study were analyzed with a frequency distribution tabulated and tested with the Pearson Product Moment Test. The results of this study worker who were exposed to noise intensity ≤85 dBA had a normal blood pressure of 8 (36.5%) people, in workers who were exposed to noise intensity ≤85 dBA had blood pressure with Pre-hypertension as many as 12 (54.5% ) people, for workers exposed to noise intensity ≤85 dBA have 1 (4.5%) blood pressure with Stage 1 Hypertension, workers who are exposed to noise intensity ≤85 dBA have blood pressure with Stage 2 Hypertension as much as 1 (4.5 %) person. While workers who are exposed to noise intensity> 85 dBA have normal blood pressure of 0 (0%) people, workers who are exposed to noise intensity> 85 dBA have blood pressure with Pre-hypertension as much as 2 (5.1%) people, workers are exposed to noise intensity> 85 dBA had blood pressure with Stage 1 Hypertension as many as 14 (35.9%) people, then workers exposed to noise intensity> 85 dBA had blood pressure with Stage 2 Hypertension as many as 23 (59%) workers. The results of the Pearson Product Moment analysis value of p = 0,000 <α 0.05, there is a relationship between noise intensity and blood pressure with the magnitude of the correlation coefficient (r) which is 0.795 meaning, there is a strong relationship. Based on this study it can be concluded that there is a significant relationship between noise intensity and blood pressure.